Comparison of Mycoplasma pneumoniae Genome Sequences from Strains Isolated from Symptomatic and Asymptomatic Patients - Spuesens, Emiel B. M.; Brouwer, Rutger W. W.; Mol, Kristin H. J. M.; Hoogenboezem, Theo; Kockx, Christel E. M.; Jansen, Ruud; Van IJcken, Wilfred F. J.; Van Rossum, Annemarie M. C.; Vink, Cornelis (Frontiers in Microbiology, 2016)
Mycoplasma pneumoniae is a common cause of respiratory tract infections (RTI) in children. We recently demonstrated that this bacterium can be carried asymptomatically in the respiratory tract of children. To identify potential genetic differences between M. pneumoniae strains that are carried asymptomatically and those that cause symptomatic infections, we performed whole-genome sequence analysis of 20 M. pneumoniae strains. The analyzed strains included 3 reference strains, 3 strains isolated from asymptomatic children, 13 strains isolated from clinically well-defined patients suffering from an upper (n=4) or lower (n=9) RTI, and one strain isolated from a follow-up patient who recently recovered from an RTI. The obtained sequences were each compared to the sequences of the reference strains. To find differences between strains isolated from asymptomatic and symptomatic individuals, a variant comparison was performed between the different groups of strains. Irrespective of the group (asymptomatic versus symptomatic) from which the strains originated, subtype 1 and subtype 2 strains formed separate clusters. We could not identify a specific genotype associated with M. pneumoniae virulence. However, we found marked genetic differences between clinical isolates and the reference strains, which indicated that the latter strains may not be regarded as appropriate representatives of circulating M. pneumoniae strains.